2017
DOI: 10.1097/qad.0000000000001545
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperinsulinemia effects on systemic markers of immune activation in HIV

Abstract: Summary The well-treated HIV population remains at risk for insulin resistance and chronic immune activation. We tested the effects of acute hyperinsulinemia on inflammation in HIV. Twenty HIV-infected and 10 non-HIV-infected individuals well-matched for BMI underwent oral glucose tolerance testing to stimulate insulin secretion and assess for changes in circulating sCD163, sCD14, and MCP-1. sCD14 decreased significantly after stimulation of hyperinsulinemia and no significant changes in sCD163 or MCP-1 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Insulin resistance has been widely reported in adults with HIV [37] and inflammation and immune activation, which have been associated with non-AIDS complications in HIV. Specifically, higher insulin resistance, as measured by HOMA-IR or oral glucose tolerance test in HIV, has been associated with classical monocyte subsets and monocyte activation [12,38] and with bacterial translocation [39][40][41] but not gut barrier dysfunction [42]. We have previously published that this Ugandan cohort with PHIV has increased T cell activation and evidence of a leaky gut compared with children without HIV, which worsened over time [43,44]; however, in this analysis, none of the markers of systemic inflammation, immune activation, gut integrity, or translocation were associated with HOMA-IR in PHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance has been widely reported in adults with HIV [37] and inflammation and immune activation, which have been associated with non-AIDS complications in HIV. Specifically, higher insulin resistance, as measured by HOMA-IR or oral glucose tolerance test in HIV, has been associated with classical monocyte subsets and monocyte activation [12,38] and with bacterial translocation [39][40][41] but not gut barrier dysfunction [42]. We have previously published that this Ugandan cohort with PHIV has increased T cell activation and evidence of a leaky gut compared with children without HIV, which worsened over time [43,44]; however, in this analysis, none of the markers of systemic inflammation, immune activation, gut integrity, or translocation were associated with HOMA-IR in PHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence over the last several years has highlighted the potential contribution of an impaired gut microbial barrier and translocated bacterial products to sequelae of chronic inflammation and immune activation in persons with HIV [71, 72]. Acute hyperinsulinemia during OGTT in persons with and without HIV was associated with increases in soluble CD14, a marker of monocyte activation related to lipopolysaccharide (LPS) [73]. Other recent studies have reported correlations between higher IR (by OGTT) and plasma LPS level in persons on ART [74], and between the presence of bacterial DNA products and elevations of hemoglobin A1c over time [75].…”
Section: Risk Factors For Insulin Resistance Potentially Unique To Ormentioning
confidence: 99%